Workflow scheduling - Agarwal, Kanika (2013)
The booming technological industry, currently witnesses a rising competition between telecommunication giants, web service providers and software solution companies etc. All are striving to emerge on the top in terms of how satisfied their customers are and the business impact they are making. They are deploying huge systems and running large processes to ensure a smooth service for their clients and this in result is generating billions of loosely structured data which the traditional systems and the warehouses cannot sustain any more. Thus, “Big Data” [1] technologies are needed which help in processing such big data several times faster than the traditional methods.